2022
DOI: 10.1121/10.0011094
|View full text |Cite
|
Sign up to set email alerts
|

Managing occupational noise from blasts

Abstract: The aim of this work is to examine the current best practice for the assessment of auditory hazards associated with occupational impulsive noise for a UK-based test site. A summary of the literature is presented on the measurement methodologies, hearing conservation, and relevant guidance for the selection of hearing protection within the context of near-field impulsive noise. The current U,K. best practice recommends the adapted HML method from Defence Standard 0027:2015 using a C-peak measurement of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…An evaluation of the performance of an existing heuristic prediction model, the SSW model from [1], was performed on longitudinal data gathered by the LMN. The model's ability to predict impacts from industrial operations beyond its development scope was presented in [11]. This work found that up to 5 days ahead of testing, the SSW model had root-mean-square errors for receivers at a range of 4-14km of approximately 10dB for EDH and Pad C explosions and approximately 7.5dB for CVE and HYD associated with hazard awareness training.…”
Section: Live Monitoring Network (Lmn)mentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation of the performance of an existing heuristic prediction model, the SSW model from [1], was performed on longitudinal data gathered by the LMN. The model's ability to predict impacts from industrial operations beyond its development scope was presented in [11]. This work found that up to 5 days ahead of testing, the SSW model had root-mean-square errors for receivers at a range of 4-14km of approximately 10dB for EDH and Pad C explosions and approximately 7.5dB for CVE and HYD associated with hazard awareness training.…”
Section: Live Monitoring Network (Lmn)mentioning
confidence: 99%
“…A short series of field trials in 2017, known as DABENIM (Development of A Bespoke Environmental Noise Impact Method), identified issues with the accuracy and speed of prediction and highlighted the need to develop new heuristic prediction methods. This led to the most recent and current work [9][10][11] through an industrially-sponsored PhD at Spadeadam, which is expanded upon in section 4.…”
Section: Measurementmentioning
confidence: 99%